Does the future of a farm depend on its neighbourhood? Evidence on intra-family succession among fruit and vegetable farms in Italy - Daniele Cavicchioli; Danilo Bertoni; Dario Gianfranco Frisio; Roberto Pretolani (Agricultural and Food Economics, 2019)
The transfer of farm activity over time occurs through different pathways, among which the more frequent is intra-family farm succession. Thus, better information on farm succession determinants is crucial for understanding farm succession and informing appropriate sectoral policies. To date, substantial research has focused on the effect of farm, farmer and potential heir features on farm succession, while the role played by socio-economic conditions around a farm has been relatively less examined. Building on previous contributions, the present paper considers farm succession as the opposite of labour migration out of the agricultural sector. Thus, the effect of the labour market and surrounding conditions (LMSC) around a farm on its succession probability is explored. The aim of this paper is therefore to explore whether and to what extent the inclusion of LMSC variables may contribute to a better understanding of farm succession. Using data from a sample of 266 fruit and vegetable farms (gathered for informative purposes by a producers' organization consortium), empirical evidence that LMSC variables play an important role in explaining the succession probability in these types of farms is provided. Specifically, the results show that (i) including LMSC variables in a farm succession analysis increases the explanatory power and robustness of the model estimates; (ii) LMSC variables have a non-linear effect on succession; and (iii) some explanatory variables (farmer education and farm age, specialization and dimension) are significant across various specifications, while other variables (farmer age, territorial location and distance of a farm from its producer organization) change their sign and/or significance when LMSC variables are included in the model. As a consequence, our findings suggest that LMSC variables should be included in farm succession and labour market analysis to provide a better estimate of farm succession probability.
Keywords: J62; J43; Q12; R12; 330; Farm transfer; Local labour market; Out-farm migration; Occupational choice theory